Fiducia-warranty in the Romanian law - a possible practical transposition from the French law? - Chirieac, Roxana (Technium Social Sciences Journal, 2020)
The fiducia is an institution of long standing tradition in the civil law systems, being regulated in these ever since the roman law period. But, by the assuming the Napoleon French Civil Code, the fiducia was taken out of the regulations of our country, until the entry into force of the 2011 Civil Code. Then, our legislator decided to acquire the French regulations and reintroduce in the national regulations the fiducia institution. Unfortunately, the institution did not come to know success – although meant to compete with the Anglo-Saxon trust, at the present moment there are up to 200 fiducia registered in Romania. On the opposite side, almost 20% of Americans owns a type of trust. The circumstances in Romania are similar to those in France, where the current regulation of the fiducia was „conceived”, where scholars as well as practitioners have tried the implementation of different variations of the fiducia in order to make the institution applicable. Thus were created fiducia-warranty (fiducie sûreté), fiducia management (fiducie gestion), and scholars have spoke about fiducia concessionary (fiducie libéralité). The present study aims to analyse the fiducia warranty institution and to suggest a „transposition” of this practice in the Romanian legislation. We do not consider that the fiducia will generate as much enthusiasm as the trust, that is much more flexible in its constitution as well as its exploitation, but we consider that it may develop its application in our national legislation.